Storytelling as a strategy for developing student concentration in non-formal schools - William Winanto; Widiyanto Widiyanto; Komang Sutawan (International Journal of Science and Applied Science: Conference Series, 2025)
Children's concentration in learning is an important factor in the success of the learning process, especially in non-formal educational environments such as Buddhist Sunday School (SMB). One approach that can be used to improve children's concentration is the storytelling approach. This study aims to determine the effect of the storytelling approach on the concentration of Mahakusala SMB children in understanding the Buddhist teachings delivered in class. The method used in this study is a quantitative approach with an observational research design and the use of a questionnaire as a concentration measurement tool. The subjects in this study were 30 children aged 10–13 years old from Mahakusala Buddhist Sunday School (SMB). Based on data collected through direct observation during the storytelling process and the completion of questionnaires that had been tested for validity and reliability, the findings highlight the potential of storytelling not only as an engaging teaching strategy but also as a practical tool for improving student focus. Applying the storytelling approach in other Buddhist Sunday schools (SMB) can produce similar improvements, supporting educators in fostering better attention and deeper understanding among students. The results of this study show a positive and significant effect of the storytelling approach on children's concentration. This is evidenced by an R square value of 0.973, which means that 97.3% of the variation in children's concentration can be explained by the use of the storytelling approach, while 2.7% is influenced by other factors. Thus, the storytelling approach has been proven to be more effective in improving children's concentration in learning activities at Mahakusala SMB and can be recommended for use as the main strategy in Dhamma learning.